A CLN8 biallelic missense variant causes epilepsy with severe treatment-resistant psychosis - Rimsha Zulfiqar; Ambreen Kanwal; Maham Hameed; Amina Iftikhar; Go Hun Seo; Sadaf Naz (Molecular Genetics and Genomics, 2026)

Synergistic decontamination of Salmonella spp. in raw almonds using phytic acid and drying as an eco-friendly alternative to propylene oxide - Go Hun Seo; Hary Yu; Min Suk Rhee (Food Research International, 2025)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

PKHD1L1, a gene involved in the stereocilia coat, causes autosomal recessive nonsyndromic hearing loss - Shelby E. Redfield; Pedro De-la-Torre; Mina Zamani; Hanjun Wang; Hina Khan; Tyler Morris; Gholamreza Shariati; Majid Karimi; Margaret A. Kenna; Go Hun Seo; Hongen Xu; Wei Lu; et al. (Human Genetics, 2024)
Identification of genes associated with nonsyndromic hearing loss is a crucial endeavor given the substantial number of individuals who remain without a diagnosis after even the most advanced genetic testing. PKHD1L1 was established as necessary for the formation of the cochlear hair-cell stereociliary coat and causes hearing loss in mice and zebrafish when mutated. We sought to determine if biallelic variants in PKHD1L1 also cause hearing loss in humans. Exome sequencing was performed on DNA of four families segregating autosomal recessive nonsyndromic sensorineural hearing loss. Compound heterozygous p.[(Gly129Ser)];p.[(Gly1314Val)] and p.[(Gly605Arg)];p[(Leu2818TyrfsTer5)], homozygous missense p.(His2479Gln) and nonsense p.(Arg3381Ter) variants were identified in PKHD1L1 that were predicted to be damaging using in silico pathogenicity prediction methods. In vitro functional analysis of two missense variants was performed using purified recombinant PKHD1L1 protein fragments. We then evaluated protein thermodynamic stability with and without the missense variants found in one of the families and performed a minigene splicing assay for another variant. In silico molecular modeling using AlphaFold2 and protein sequence alignment analysis were carried out to further explore potential variant effects on structure. In vitro functional assessment indicated that both engineered PKHD1L1 p.(Gly129Ser) and p.(Gly1314Val) mutant constructs significantly reduced the folding and structural stabilities of the expressed protein fragments, providing further evidence to support pathogenicity of these variants. Minigene assay of the c.1813G>A p.(Gly605Arg) variant, located at the boundary of exon 17, revealed exon skipping leading to an in-frame deletion of 48 amino acids. In silico molecular modeling exposed key structural features that might suggest PKHD1L1 protein destabilization. Multiple lines of evidence collectively associate PKHD1L1 with nonsyndromic mild–moderate to severe sensorineural hearing loss. PKHD1L1 testing in individuals with mild–moderate hearing loss may identify further affected families.

Skewed X-chromosome Inactivation in Women with Idiopathic Intellectual Disability is Indicative of Pathogenic Variants - Luiza D. Chaves; Laura M. L. Carvalho; Giovanna C. Tolezano; Sara F. Pires; Silvia S. Costa; Marília O. de Scliar; Liane de R. Giuliani; Debora R. Bertola; Cíntia B. Santos-Rebouças; Go Hun Seo; Paulo A. Otto; Carla Rosenberg; et al. (Molecular Neurobiology, 2023)

Ascorbic Acid Supplementation Prevents the Detrimental Effects of Prenatal and Postnatal Lead Exposure on the Purkinje Cell and Related Proteins in the Cerebellum of Developing Rats - Sung Min Nam; Jin Seok Seo; Tae-Hun Go; Sang-Soep Nahm; Byung-Joon Chang (Biological Trace Element Research, 2019)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Ascorbic Acid Ameliorates Gestational Lead Exposure-Induced Developmental Alteration in GAD67 and c-Kit Expression in the Rat Cerebellar Cortex - Sung Min Nam; Sung Chuel Ahn; Tae-Hun Go; Jin Seok Seo; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2018)